1993
DOI: 10.1103/physrevlett.70.449
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure of the (310) twin in niobium: Experimental determination and comparison with theoretical predictions

Abstract: The atomic structure of the (310) twin in Nb was predicted using interatomic potentials derived from the embedded atom method (EAM), Finnis-Sinclair theory (FS), and the model generalized pseudopotential theory (MGPT). The EAM and FS predicted structures with crystal translations which break mirror symmetry. The MGPT predicted one stable structure which possessed mirror symmetry. This defect was experimentally determined to have mirror symmetry. These findings emphasize that the angular dependent interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…The results of the present study on Ta, when combined with previously reported results on Nb [8] and MO [9], reaffirms the predictive power of the MGPT derived potentials for modeling defect structures in the BCC metals.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The results of the present study on Ta, when combined with previously reported results on Nb [8] and MO [9], reaffirms the predictive power of the MGPT derived potentials for modeling defect structures in the BCC metals.…”
Section: Discussionsupporting
confidence: 64%
“…The model of interatomic interactions with angular dependence that we use is the Model Generalized Psuedopotential Theory (MGPT) [5]. We have applied it to modeling the x5 (3 1 O)/[OO 1 ] symmetric tilt grain boundary (STGB) in niobium [8], molybdenum [9], and tantalum as a critical test of its accuracy. We report here on the results for Ta.…”
mentioning
confidence: 99%
“…[18,19] where classical potentials identify non-physical minimum energy grain boundary structures. The minimum energy structure identified by embedded atom potentials has a tendency to favour structures preserving the coordination number at the interface.…”
Section: Specificationmentioning
confidence: 99%
“…The rapid development of computers enables such simulations to be carried out presently for systems with about i06 atoms on conventional workstations, and with up to i0 9 atoms and short-range interatomic interactions on massively parallel supercomputers. Examples of successful studies for materials include determinations of atomic arrangements along grain boundaries, of dislocation core structures, or of atomic structures and dynamical propagations of crack tips in metals, semiconductors and ionic crystals.…”
Section: Introductionmentioning
confidence: 99%